Butyrate increases intracellular calcium levels and enhances growth hormone release from rat anterior pituitary cells via the G-protein-coupled receptors GPR41 and 43. - Maria Consolata Miletta (Public Library of Science (PLoS), 2014)
Butyrate is a short-chain fatty acid (SCFA) closely related to the ketone body ß-hydroxybutyrate (BHB), which is considered to be the major energy substrate during prolonged exercise or starvation. During fasting, serum growth hormone (GH) rises concomitantly with the accumulation of BHB and butyrate. Interactions between GH, ketone bodies and SCFA during the metabolic adaptation to fasting have been poorly investigated to date. In this study, we examined the effect of butyrate, an endogenous agonist for the two G-protein-coupled receptors (GPCR), GPR41 and 43, on non-stimulated and GH-releasing hormone (GHRH)-stimulated hGH secretion. Furthermore, we investigated the potential role of GPR41 and 43 on the generation of butyrate-induced intracellular Ca2+ signal and its ultimate impact on hGH secretion. To study this, wt-hGH was transfected into a rat pituitary tumour cell line stably expressing the human GHRH receptor. Treatment with butyrate promoted hGH synthesis and improved basal and GHRH-induced hGH-secretion. By acting through GPR41 and 43, butyrate enhanced intracellular free cytosolic Ca2+. Gene-specific silencing of these receptors led to a partial inhibition of the butyrate-induced intracellular Ca2+ rise resulting in a decrease of hGH secretion. This study suggests that butyrate is a metabolic intermediary, which contributes to the secretion and, therefore, to the metabolic actions of GH during fasting.